Fertility and sexual dysfunction issues in adults with genitourinary congenital anomalies. Issue 4 (July 2016) - Trofimenko, Vera; Brant, William O.
Abstract : Purpose of review: As growing numbers of adolescents with a history of congenital genitourinary anomalies successfully enter adulthood, their spectrum of urologic concerns broadens to include sexual function and reproduction. Recent findings: In hypospadias repair, preoperative testosterone was found to reduce rates of postoperative complications of urethrocutaneous fistula formation and meatal stenosis. Following hypospadias correction, dissatisfaction with surgical outcomes has been observed to correlate with psychological outcomes, rather than objective measurements such as location of meatus degree of curvature. In women with a congenital absence of a vagina, sigmoid vaginoplasty and dilation yield similar sexual outcomes, however, vaginoplasty was associated with a 20% rate of reoperation. Ilioinguinal-to-dorsal neurorrhaphy for restoration of penile sensation in myelomeningocele has shown success in a small pilot study. Both sexual activity and paternity rates are higher in women, compared with men who are born with bladder exstrophy. Summary: The extent and complexity of issues related to sexual function and fertility in the population of patients with a history of genitourinary malformation requires a thoughtful approach to timely surgical management and consistent care through their transition from childhood to adulthood.